Analysis of the Effect of Security, Effectiveness, and Ease of BTN Mobile Services on the Mobile Banking Marketing Strategy of PT Bank Tabungan Negara (Persero) Tbk Yogyakarta Branch - Salsabila, Khoirunnisa; Albari, Albari (SENTRALISASI, 2024)
This study aims to determine the influence of service security factors, service effectiveness, and service security in marketing strategies for PT Bank Tabungan Negara or Bank BTN KC Yogyakarta customers. This study uses a quantitative approach using the Accidental Sampling technique, which produces 100 samples. The data analysis technique is processed using IBM SPSS 26 software. The results of the study indicate that service security and service effectiveness at BTN Mobile have a significant positive effect on mobile banking marketing strategies, while ease of service does not have an influence on the mobile banking marketing strategy. This research is useful to help banks understand what factors influence marketing strategies in using mobile banking services to improve their mobile banking services so that they better meet customer needs and desires such as security, effectiveness, and ease of mobile banking services.